A criação da Comissão Econômica para a América Latina e o Caribe: um think tank econômico na periferia do capitalismo: The creation of the Economic Commission for Latin America and the Caribbean: an economic think tank on the periphery of capitalism (Revista de História da UEG (REVHIST), 2020)
This paper aims to present a historical analysis of the factors that contributed to the conception of a theory of underdevelopment and the creation of the Economic Commission for Latin America and the Caribbean. The post-World War II historical-economic conjecture that culminated in the United States hegemony and the formation of international organizations and regional commissions related to the United Nations is presented. ECLAC´s structuralist ideal is understood, mainly, from the thinking of the Argentine economist Raúl Prebisch. Thus, a historical overview of the factors that led Prebisch to the creation and consolidation of structuralist theory as the basis of ECLAC´s thinking that would affect public policy proposals for the Latin American region over time will be presented.Keywords: ECLAC; structuralism; Raúl Prebisch.